Comparative efficacy of five approved Janus kinase inhibitors as monotherapy and combination therapy in patients with moderate-to-severe active rheumatoid arthritis: a systematic review and network meta-analysis of randomized controlled trials - Wenting Cai; Wenting Cai; Rui Tong; Rui Tong; Yue Sun; Yao Yao; Jinping Zhang (Frontiers Media S.A., 2024)
BackgroundThe European League of Rheumatology(EULAR)guidelines recommend Janus kinase (JAK) inhibitors for patients with moderate to severe rheumatoid arthritis (RA) who are insensitive or under-responsive to conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs). But there was no recommendation for which one was preferred in five currently approved JAK inhibitors. The objective of this network meta-analysis study was to evaluate the efficacy of five JAK inhibitors as monotherapy and combination therapy in patients with moderate-to-severe active rheumatoid arthritis.MethodsThe randomized controlled trials (RCTs) of tofacitinib, baricitinib, upadacitinib, filgotinib and peficitinib as monotherapy or combined with csDMARD in the treatment of active RA were searched in database of PubMed, Embase, Web of Science and Cochrane Library, up to December 2023. The control group included placebo or csDMARD. Outcome indicators included American College of Rheumatology 20% response (ACR20), ACR50, ACR70 and the percentage of patients achieving 28-joint disease activity score using C-reactive protein (DAS28(CRP))<2.6 at 12 weeks and 24 weeks. The statistical analysis was performed by Stata14 and RevMan5.4. Data processing, network evidence plots, surface under the cumulative ranking curve (SUCRA) ranking, league plots and funnel plots were generated. Risk ratio (RR) and 95% confidence interval (95%CI) as effect sizes to analyze the statistics.ResultsThis study included thirty-six RCTs with 16,713 patients. All JAK inhibitors were more effective than placebo in ACR20 (RRs ranging between 1.74 and 3.08), ACR50 (RRs ranging between 2.02 and 7.47), ACR70 (RRs ranging between 2.68 and 18.13), DAS28(CRP) < 2.6 (RRs ranging between 2.70 and 7.09) at 12 weeks. Upadacitinib 30 mg and upadacitinib 15 mg showed relatively good efficacy according to their relative SUCRA ranking. All JAK inhibitors were more effective than csDMARD or placebo in ACR20 (RRs ranging between 1.16 and 1.86), ACR50 (RRs ranging between 1.69 and 2.84), ACR70 (RRs ranging between 1.50 and 4.47), DAS28(CRP) < 2.6 (RRs ranging between 2.28 and 7.56) at 24 weeks. Upadacitinib 15 mg + csDMARD and baricitinib 4 mg + csDMARD showed relatively good efficacy according to their relative SUCRA ranking. The safety analysis results such as serious infection, malignancy, major adverse cardiovascular event (MACE), and venous thromboembolic events (VTE) showed no statistical difference.ConclusionThis NMA study indicated that all JAK inhibitors performed better than placebo. Based on the results of this study, upadacitinib 30 mg, upadacitinib 15 mg, upadacitinib 15 mg + csDMARD and baricitinib 4 mg + csDMARD were recommended treatment options with relatively good efficacy and safety. However, attention should be paid to monitoring the occurrence of adverse events in high-risk RA patients with medication. Combination therapy with csDMARD might be more suitable for the maintenance of long-term efficacy. However, in clinical practice, it is still necessary to select the appropriate therapeutic regimen based on the actual clinical situation.